ANALISIS STRUKTUR MODAL & FAKTOR YANG MEMPENGARUHINYA PADA SUB SEKTOR PROPERTI & REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2011-2015 - Yuhelmi Yuhelmi (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2018)
This study aims to analyze the Capital Structure as well as factors that affect it on the company in Sub Sector Property & Real Estate listed on the Indonesia Stock Exchangeperiod 2011 to 2015. The sampling technique in this study is the technique of Full Samplingwhere all the population into a sample that is as many as 26 companies. The analytical method used to test the factors affecting the Capital Structure is Multiple Linear Regression and using t Test.This study found that profitability and asset structure has no significant effect on Capital Structure while firm size has positive effect on Capital Structure.